A fungal natural product that inhibits plant cellulose biosynthesis by disrupting cellulose synthase complexes - Zhongshou Wu; Lu Liu; Wenyu Han; Xingbo Cai; Pixian Xiao; Zuodong Sun; Chunsheng Yan; Silvana Reid; Yun Chen; Zhonghua Ma; Yi Tang; Steven E. Jacobsen (Proceedings of the National Academy of Sciences, 2026)
Cellulose, a primary component of plant cell walls, is synthesized by cellulose synthase complexes (CSCs) at the plasma membrane. Targeting this process with cellulose biosynthesis inhibitors (CBIs) has significantly advanced our understanding of plant cell wall formation and provided valuable compounds for herbicide development. Here, we identified a fungal natural product, 8-methyldichlorodiaporthin (MDD), as a broad-spectrum plant CBI. Structure–activity relationship analyses demonstrate that methylation modifications on the isocoumarin ring and chlorination of the side chain are crucial for MDD-induced growth inhibition. A chemical forward genetic screen in Arabidopsis thaliana revealed two semidominant CESA1 mutations, causing A903T and H1024Y substitutions, that confer insensitivity to MDD. Both mutations locate to transmembrane domains of CESA1, and we show that MDD depletes CSCs from the plasma membrane and reduces cellulose content. Further genetic analyses indicate that the cesa1 mddi1-1 A903T mutant also confers resistance to CBIs quinoxyphen and C17, but not to CBIs isoxaben, indaziflam, or ES20. Stacking additional point mutations conferring resistance to other CBIs, cesa3 ixr1-1 G998D , and cesa6 es20-r3 G935E into the cesa1 mddi1-1 A903T background yields multiple-drug-resistant lines that maintain normal growth. These findings establish MDD, as a natural CBI that likely targets CESA1, thereby extending our understanding of CSC regulation and abilities to develop multidrug-resistant crop varieties. These findings offer unique perspectives for weed management and plant biotechnology.